A cow‐level association of ruminal pH on body condition score, serum beta‐hydroxybutyrate and postpartum disorders in Thai dairy cattle. (24th June 2014) - Chaidate, Inchaisri; Somchai, Chanpongsang; Jos, Noordhuizen; Henk, Hogeveen
Abstract Subacute ruminal acidosis in dairy cows occurs when ruminal pH is below about 5.5. However, the exact threshold level of ruminal pH affecting cow health is still in debate. This investigation was carried out in 505 cows within 31 farms. The postpartum disorders, including dystocia, retained placenta, anestrus, cystic ovary, metritis, clinical mastitis and lameness, were analyzed. Ruminal pH, serum beta‐hydroxy butyrate (SBHB), serum urea nitrogen and body condition score (BCS) were measured once during the 3 to 6 weeks postpartum, while BCS was determined once more at 1 week before calving. Ruminal pH was determinded by ruminocentesis technique. The ruminal pH was evaluated to study the association with BCS, SBHB and postpartum disorders using linear regression in a generalized linear mixed model with farm as a random effect. The results show that low ruminal pH was associated with dystocia, metritis and lameness. Moreover, a low ruminal pH can be found in cows with a high loss of BCS after calving and also in cows with low SBHB postpartum. These findings confirmed the feasibility of the ruminocentesis technique and the association of low ruminal pH on various postpartum disorders at the individual cow level. However, the consequences of low ruminal pH on dairy cow health still needs more exploration for a better understanding of the physiological mechanisms.